Effective Surgical Management of Femoralhead Affections in Dogs: Review of Ten Cases - , Puli Vishnu Vardhan Reddy; , Pushkin Raj; , Mohammed Shafiuzama; , Shiju Simon; Sindhu R.,; Saran S., (Archives of Current Research International, 2024)
Ten dogs suffering from various conditions affecting the coxofemoral joint, including hip dysplasia, hip luxation, and femoral capital fractures, were included in the study. Nine of these dogs underwent treatment with femoral head osteotomy, while one case of hip luxation was treated using a toggle technique. All procedures involved a cranio-lateral incision approach and osteotomy performed with an oscillating saw. Following physiotherapy and passive range of motion exercises, all the dogs exhibited pain-free ambulation. The simple Femoral Head Ostectomy surgery effectively manages various femoral head affections, alleviating pain and leading to a significant improvement in the quality of life.